Development of a polyacrylamide/chitosan composite hydrogel conduit containing synergistic cues of elasticity and topographies for promoting peripheral nerve regeneration. (21st July 2022) - Liu, Fang; Xu, Jiawei; Liu, Anning; Wu, Linliang; Wang, Dongzhi; Han, Qi; Zheng, Tiantian; Wang, Feiran; Kong, Yan; Li, Guicai; Li, Peng; Gu, Shouyong; et al.
Abstract : The polyacrylamide/chitosan composite hydrogel containing synergistic cues of elasticity and topographies was developed by  in situ  free radical polymerization and micromolding methods. Abstract : Substrate elasticity and topographical guidance are crucial factors for regulating tissue regeneration, but the synergistic effects of both cues on peripheral nerve regeneration are still unclear. In this paper, polyacrylamide/chitosan (PAM/CS) composite hydrogels with synergistic characteristics of elasticity and morphology were prepared using in situ free-radical polymerization and micro-molding. The physicochemical properties of hydrogels were characterized, and the effect on peripheral nerve regeneration was systematically evaluated via in vitro and in vivo experiments, respectively. The in vitro experiments showed that on a PAM/CS composite hydrogel with an elastic modulus of 5.822 kPa/8.41 kPa and a surface groove width of 30 μm, the dorsal root ganglion (DRG) neurite had a strong growth ability and better-oriented status. The samples were taken from each group at 2 and 12 weeks after bridging rabbit sciatic nerve defects with a PAM/CS composite hydrogel conduit. General observation of the rabbit body and transplanted nerve, nerve electro-physiological examination, muscle wet weight recovery rate detection and comparison, observation of sciatic nerve frozen section immunofluorescence staining and myelinated nerve fiber recovery rate comparison were used to evaluate the effect of nerve transplantation. The elastic modulus of 8.41 kPa and groove width of 30 μm were similar to those of the autograft group. At the same time, the signaling pathways, including the focal adhesion markers vinculin, p-FAK, and Rho A protein, referring to axon adhesion and extension, were initially revealed. In summary, our developed hydrogel implants containing synergistic cues of elasticity and topographies may provide a new and effective strategy for the treatment of peripheral nerve injury in the future.